Production process for biodegradable plastic and application thereof

The production process for biodegradable plastics enhances crystallization and flame retardancy by using flame retardant microspheres and modified fillers, addressing the limitations of conventional additives and improving mechanical properties.

CN119242005APending Publication Date: 2025-01-03河北雄安骅洋纸塑包装实业有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411439846.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Polylactic acid-based biodegradable plastics suffer from poor crystallization performance, thermal stability, and flame retardancy, with the addition of conventional additives compromising biodegradability and leading to additive precipitation.

Method used

A production process involving flame retardant microspheres and modified fillers, where flame retardant microspheres are prepared using copolymer microspheres with ionic bonds and modified fillers are grafted onto calcium carbonate whiskers, enhancing crystallization and mechanical properties while maintaining biodegradability.

Benefits of technology

Improves the crystallization and flame retardancy of biodegradable plastics, preventing additive precipitation and extending service life without reducing biodegradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005086059970000131
    Figure BDA0005086059970000131
Patent Text Reader

Abstract

The invention relates to the field of plastics, in particular to a production process and application of biodegradable plastics, the biodegradable plastics are prepared from, by weight, 60-70 parts of polylactic acid, 3-4 parts of flame-retardant microspheres and 5-6 parts of modified filler, phytic acid and nickel ions are introduced into the flame-retardant microspheres, a triazine group and a glucose structure are introduced into the modified filler, and the flame-retardant microspheres are prepared. Therefore, the problems of poor crystallization performance and flame retardance of existing polylactic acid for biodegradable plastics are solved, meanwhile, breakable sulfonate groups are introduced into the flame-retardant microspheres, the problem that the biodegradability of the plastics is reduced due to addition of auxiliaries is avoided, precipitation of the auxiliaries in the using process is reduced, and the service life of the plastics is prolonged. The service life of the biodegradable plastic is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of plastics, and in particular to a production process for biodegradable plastics and application thereof. Background Art

[0002] In recent years, with the depletion of oil resources and the increasingly prominent white pollution problem, biodegradable polymers extracted from renewable resources have received more and more attention. Polylactic acid has been widely used in green packaging, textiles, medical care, automobiles and other fields due to its good biodegradability, mechanical properties, biocompatibility and other advantages. It is one of the most promising biodegradable polymers.

[0003] However, the poor crystallization performance of polylactic acid leads to poor thermal stability and insufficient toughness. At the same time, polylactic acid also has the disadvantage of poor flame retardancy. During the combustion process, it is very easy to have droplets, which greatly limits the application and development of polylactic acid. At present, plasticizers and flame retardants are usually added to improve the problems of poor thermal stability, insufficient toughness and insufficient flame retardancy of polylactic acid. However, plasticizers and flame retardant additives are usually low molecular weight organic or inorganic compounds. These materials have poor biodegradability, which leads to a significant reduction in the biodegradability of polylactic acid materials. At the same time, low molecular weight additives are very easy to precipitate during long-term use, which reduces the service life of polylactic acid and cannot meet market demand. Summary of the invention

[0004] The purpose of the present invention is to provide a production process for biodegradable plastics and its application, which solves the problems of poor crystallization performance and flame retardancy of polylactic acid used in existing biodegradable plastics, while avoiding the problem of reduced biodegradability of plastics due to the addition of additives, and reduces the precipitation of additives during use, thereby increasing the service life of biodegradable plastics.

[0005] The object of the present invention can be achieved by the following technical scheme: A production process for biodegradable plastics, comprising the following steps: weighing the following raw materials by weight: 60-70 parts of polylactic acid, 3-4 parts of flame retardant microspheres and 5-6 parts of modified fillers, mixing the polylactic acid, the flame retardant microspheres and the modified fillers, mixing for 10 minutes at a stirring rate of 50 rpm and a temperature of 180° C., discharging the materials, and preparing a biodegradable plastic;

[0006] An application for biodegradable plastics, comprising the following steps: feeding the biodegradable plastics into a film-making machine, preheating the plastics at a preheating temperature of 190° C. for 5 minutes, hot pressing for 1 minute at a pressure of 10 MPa, and then annealing for 30 minutes at a temperature of 110° C. and a pressure of 10 MPa to obtain a biodegradable film;

[0007] The flame retardant microspheres are prepared by the following steps:

[0008] Step A1: 4-bromo-1-butene, sodium sulfate and deionized water are mixed, and the mixture is reacted for 10-12 hours at a stirring rate of 120-150 rpm and a temperature of 80°C, cooled, filtered, and a filter cake is obtained. The filter cake is mixed with phosphorus oxychloride, and the mixture is reacted for 1-1.5 hours at a stirring rate of 120-150 rpm and a temperature of 120°C under nitrogen protection to obtain an intermediate a. 3-butene-1-ol, 4-dimethylaminopyridine, triethylamine and dichloromethane are mixed, and the mixture is stirred at a stirring rate of 120-150 rpm and a temperature of 5°C, and the intermediate a is added thereto for a reaction of 1-1.5 hours to obtain an intermediate b.

[0009] The dosage ratio of 4-bromo-1-butene, sodium sulfate, deionized water and phosphorus oxychloride is 0.03-0.035 mol: 5-7 g: 30-35 mL: 30-35 mL, and the dosage ratio of 3-butene-1-ol, 4-dimethylaminopyridine, triethylamine and intermediate a is 0.03-0.035 mol: 0.4-0.5 g: 5-6 mL: 0.03-0.035 mol;

[0010] During the reaction, bromine in 4-bromo-1-butene forms a sulfonic acid group under the action of sodium sulfate, and the sulfonic acid group forms a sulfonyl chloride group under the action of phosphorus oxychloride to obtain intermediate a, and then under the action of 4-dimethylaminopyridine and triethylamine, the sulfonyl chloride group in intermediate a reacts with the hydroxyl group in 3-butene-1-ol to form a sulfonate group to obtain intermediate b;

[0011] Step A2: Mix the intermediate b, styrene, maleic anhydride and isoamyl acetate, stir and add azobisisobutyronitrile under nitrogen protection, at a stirring rate of 100-120 rpm and a temperature of 70°C, and react for 6-8 hours to obtain copolymer microspheres, mix the copolymer microspheres with an ethanol solution, stir and add ethylenediamine at a stirring rate of 100-120 rpm and room temperature, and react for 6-8 hours to obtain amino copolymer microspheres;

[0012] The amount ratio of intermediate b, styrene, maleic anhydride, isoamyl acetate and azobisisobutyronitrile is 0.03-0.035 mol: 0.048-0.05 mol: 0.05-0.052 mol: 150-160 mL: 0.1-0.15 g, the volume fraction of the ethanol solution is 50%, and the amount ratio of the copolymer microspheres, the ethanol solution and ethylenediamine is 2-2.4 g: 50-60 mL: 0.05-0.06 mol;

[0013] During the reaction, under the action of azobisisobutyronitrile as a catalyst, free radical polymerization of double bonds in intermediate b, styrene and maleic anhydride occurs to obtain copolymer microspheres, and the anhydride groups in the copolymer microspheres react with ethylenediamine to form amide bonds and introduce amino groups to obtain amino copolymer microspheres;

[0014] Step A3: The amino copolymer microspheres and the ethanol solution are mixed, stirred at a stirring rate of 100-120 rpm and a temperature of 70° C., and a phytic acid aqueous solution is added, reacted for 12 hours, and then nickel chloride hexahydrate is added and the temperature is raised to 100° C., and the reaction is continued for 3-4 hours to obtain flame retardant microspheres;

[0015] The volume concentration of the ethanol solution is 80%, the mass concentration of the phytic acid aqueous solution is 70%, and the dosage ratio of the amino copolymer microspheres, the ethanol solution, the phytic acid aqueous solution and the nickel chloride hexahydrate is 2.2-2.5g:150-180mL:8-10mL:3-4g;

[0016] During the reaction, in the ethanol solution, the amino groups in the aminated copolymer microspheres are positively charged and thus bonded to the negatively charged phytic acid groups in the phytic acid aqueous solution by ionic bonds. When nickel chloride hexahydrate is added, the positively charged nickel ions bond to the negatively charged phytic acid groups, thereby loading nickel ions to obtain flame-retardant microspheres.

[0017] The modified filler is prepared by the following steps:

[0018] Step B1: D-gluconic acid solution, methanol and concentrated hydrochloric acid are mixed, and the mixture is reacted for 4-6 hours at a stirring rate of 180-200 rpm and a temperature of 60°C, and 2-methoxy-4-nitrobenzaldehyde is added, and the reaction is continued for 24 hours to obtain intermediate 1. Intermediate 1, palladium carbon catalyst and ethanol are mixed, and the mixture is stirred at a stirring rate of 180-200 rpm and a temperature of 90°C, and hydrazine hydrate is added, and the reaction is carried out for 12 hours to obtain intermediate 2;

[0019] The mass fraction of D-gluconic acid solution is 50%, the mass fraction of concentrated hydrochloric acid is 37%, the amount ratio of D-gluconic acid solution, methanol, concentrated hydrochloric acid and 2-methoxy-4-nitrobenzaldehyde is 115-120g:80-100mL:120-150mL:0.3-0.35mol, and the amount ratio of intermediate 1, palladium carbon catalyst and hydrazine hydrate is 0.3-0.32mol:4-5g:30-35mL;

[0020] During the reaction, the carboxyl group in D-gluconic acid first undergoes an esterification reaction with methanol to form an ester group, and its hydroxyl group then reacts with the aldehyde group in 2-methoxy-4-nitrobenzaldehyde to form an acetal structure to obtain intermediate 1. The nitro group in intermediate 1 is reduced to an amino group under the action of a palladium-carbon catalyst and hydrazine hydrate to obtain intermediate 2.

[0021] Step B2: Mix the intermediate 2, 1,4-dioxane and triethylamine, stir at a stirring rate of 200-240 rpm and a temperature of 15° C., add cyanuric chloride, react for 2-3 hours, then heat to 60° C. and add γ-aminopropyltriethoxysilane, react for 4-6 hours to obtain the intermediate 3;

[0022] The ratio of intermediate 2, triethylamine, cyanuric chloride and γ-aminopropyltriethoxysilane is 0.04-0.05 mol: 2.5 mL: 0.04-0.05 mol: 8-10 g;

[0023] During the reaction, under the condition of triethylamine as an acid-binding agent, the amino group in the intermediate 2 first undergoes a substitution reaction with the chlorine atom in cyanuric chloride, and when the temperature is raised, the amino group in the γ-aminopropyltriethoxysilane then undergoes a substitution reaction with the chlorine atom in cyanuric chloride to obtain the intermediate 3.

[0024] Step B3: Calcium carbonate whiskers, deionized water and ethanol are mixed and ultrasonically dispersed for 20 minutes, stirred at a stirring rate of 600-800 rpm and a temperature of 60° C., and intermediate 3 is added, reacted for 4-5 hours, and filtered to obtain a modified filler;

[0025] The volume ratio of deionized water to ethanol is 1:9, and the amount ratio of calcium carbonate whiskers to intermediate 3 is 2-3g:0.5-0.6g;

[0026] During the reaction, the ethoxysilane in the intermediate 3 is hydrolyzed and reacts with the hydroxyl groups on the surface of the calcium carbonate whisker, and the intermediate 3 is grafted onto the surface of the calcium carbonate whisker to obtain a modified filler;

[0027] Beneficial effects of the invention: The invention discloses a production process for biodegradable plastics and its application, which solves the problem of poor crystallization performance and flame retardant performance of the existing polylactic acid used for biodegradable plastics, and avoids the problem of reduced biodegradability of plastics due to the addition of additives, reduces the precipitation of additives during use, and improves the service life of biodegradable plastics; the flame retardant microspheres are prepared by using copolymer microspheres as a matrix and combining phytic acid and nickel ions through ionic bonds, and due to the presence of phosphorus in phytic acid, it combines with the triazine group in the modified filler to form a nitrogen-phosphorus expansion flame retardant system, and due to the introduction of nickel ions, the presence of nickel ions can promote the carbonization reaction of polylactic acid during combustion, and it combines with the nitrogen-phosphorus expansion flame retardant system to further improve the flame retardant performance of biodegradable plastics, and because the copolymer microspheres are prepared by free radical polymerization using intermediate b, styrene and maleic anhydride as monomers, and because intermediate b contains sulfonate groups, and because the sulfonate groups are similar to ester groups in structure, they can be broken under biodegradation conditions, thereby reducing the performance of the flame retardant filler on degradation performance. ; Since the modified filler is based on calcium carbonate whiskers and is connected with intermediate 2 by chemical bonds, and since intermediate 2 contains acetal groups, this group can also be broken under biodegradable conditions, and since polylactic acid is degraded into lactic acid molecules during the degradation process of biodegradable plastics, and calcium carbonate whiskers are gradually exposed during the degradation process, this causes lactic acid molecules to chemically react with calcium carbonate whiskers, not only further exposing calcium carbonate whiskers to promote the biodegradation of biodegradable plastics, but also avoiding the biodegradability of biodegradable plastics caused by the addition of auxiliary agents. Decrease, since the modified filler is based on calcium carbonate whiskers and is grafted with glucose structures, and the spherical structure of the flame-retardant microspheres and the sulfonate groups contained therein, this causes the modified filler to form an oriented arrangement in the substrate during the crystallization process of polylactic acid, thereby improving the crystallization performance of the polylactic acid substrate to a certain extent, and then improving the mechanical properties of the biodegradable plastics, and due to the hydrogen bond connection between the special structure of the flame-retardant microspheres and the polylactic acid substrate, precipitation during long-term use is avoided, thereby improving the service life of the biodegradable plastics. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1 A production process for biodegradable plastics, comprising the following steps: weighing the following raw materials by weight: 60 parts of commercially available L130 polylactic acid, 3 parts of flame retardant microspheres and 5 parts of modified fillers, mixing the polylactic acid, the flame retardant microspheres and the modified fillers, mixing for 10 minutes at a stirring rate of 50 rpm and a temperature of 180° C., discharging the materials, and preparing a biodegradable plastic;

[0030] An application for biodegradable plastics, comprising the following steps: feeding the biodegradable plastics into a film-making machine, preheating the plastics at a preheating temperature of 190° C. for 5 minutes, hot pressing for 1 minute at a pressure of 10 MPa, and then annealing for 30 minutes at a temperature of 110° C. and a pressure of 10 MPa to obtain a biodegradable film;

[0031] The flame retardant microspheres are prepared by the following steps:

[0032] Step A1: 4-bromo-1-butene, sodium sulfate and deionized water are mixed, and the mixture is reacted for 10 hours at a stirring rate of 120 rpm and a temperature of 80° C., cooled, filtered, and a filter cake is obtained. The filter cake is mixed with phosphorus oxychloride, and the mixture is reacted for 1 hour at a stirring rate of 120 rpm and a temperature of 120° C. under nitrogen protection to obtain an intermediate a. 3-butene-1-ol, 4-dimethylaminopyridine, triethylamine and dichloromethane are mixed, and the mixture is stirred at a stirring rate of 120 rpm and a temperature of 5° C., and the intermediate a is added thereto for a reaction of 1 hour to obtain an intermediate b.

[0033] The amount ratio of 4-bromo-1-butene, sodium sulfate, deionized water and phosphorus oxychloride is 0.0 mol: 5-7 g: 30 mL: 30 mL, and the amount ratio of 3-butene-1-ol, 4-dimethylaminopyridine, triethylamine and intermediate a is 0.03 mol: 0.4 g: 5 mL: 0.03 mol;

[0034] Step A2: Mix the intermediate b, styrene, maleic anhydride and isoamyl acetate, stir and add azobisisobutyronitrile under nitrogen protection, at a stirring rate of 100 rpm and a temperature of 70°C, and react for 6 hours to obtain copolymer microspheres; mix the copolymer microspheres with an ethanol solution, stir and add ethylenediamine at a stirring rate of 100 rpm and room temperature, and react for 6 hours to obtain amino copolymer microspheres;

[0035] The amount ratio of intermediate b, styrene, maleic anhydride, isoamyl acetate and azobisisobutyronitrile is 0.03 mol: 0.048 mol: 0.05 mol: 150 mL: 0.1 g, the volume fraction of the ethanol solution is 50%, and the amount ratio of the copolymer microspheres, the ethanol solution and ethylenediamine is 2 g: 50 mL: 0.05 mol;

[0036] Step A3: The amino copolymer microspheres and the ethanol solution were mixed, stirred at a stirring rate of 100 rpm and a temperature of 70° C., and the phytic acid aqueous solution was added, and the reaction was carried out for 12 hours. Then, nickel chloride hexahydrate was added and the temperature was raised to 100° C., and the reaction was continued for 3 hours to obtain flame retardant microspheres;

[0037] The volume concentration of the ethanol solution is 80%, the mass concentration of the phytic acid aqueous solution is 70%, and the dosage ratio of the amino copolymer microspheres, the ethanol solution, the phytic acid aqueous solution and the nickel chloride hexahydrate is 2.2g:150mL:8mL:3g;

[0038] The modified filler is prepared by the following steps:

[0039] Step B1: D-gluconic acid solution, methanol and concentrated hydrochloric acid were mixed, and the mixture was reacted for 4 hours at a stirring rate of 180 rpm and a temperature of 60°C, and 2-methoxy-4-nitrobenzaldehyde was added, and the reaction was continued for 24 hours to obtain intermediate 1. Intermediate 1, palladium carbon catalyst and ethanol were mixed, and the mixture was stirred at a stirring rate of 180 rpm and a temperature of 90°C, and hydrazine hydrate was added, and the reaction was continued for 12 hours to obtain intermediate 2;

[0040] The mass fraction of D-gluconic acid solution is 50%, the mass fraction of concentrated hydrochloric acid is 37%, the amount ratio of D-gluconic acid solution, methanol, concentrated hydrochloric acid and 2-methoxy-4-nitrobenzaldehyde is 115g:80mL:120mL:0.3mol, and the amount ratio of intermediate 1, palladium carbon catalyst and hydrazine hydrate is 0.3mol:4g:30mL;

[0041] Step B2: Intermediate 2, 1,4-dioxane and triethylamine were mixed, stirred at a stirring rate of 200 rpm and a temperature of 15°C, and cyanuric chloride was added, and the mixture was reacted for 2 hours. The mixture was then heated to 60°C and γ-aminopropyltriethoxysilane was added, and the mixture was reacted for 4 hours to obtain Intermediate 3;

[0042] The amount ratio of intermediate 2, triethylamine, cyanuric chloride and γ-aminopropyltriethoxysilane is 0.04 mol: 2.5 mL: 0.04 mol: 8 g;

[0043] Step B3: Mix commercially available Mayue building materials 1000 mesh calcium carbonate whiskers, deionized water and ethanol and disperse them by ultrasonication for 20 minutes, stir at a stirring rate of 600 rpm and a temperature of 60°C, add intermediate 3, react for 4 hours, filter, and obtain a modified filler;

[0044] The volume ratio of deionized water to ethanol is 1:9, and the amount ratio of calcium carbonate whisker to intermediate 3 is 2g:0.5g.

[0045] Example 2 A production process for biodegradable plastics, comprising the following steps: weighing the following raw materials by weight: 70 parts of commercially available L130 polylactic acid, 4 parts of flame retardant microspheres and 5 parts of modified fillers, mixing the polylactic acid, the flame retardant microspheres and the modified fillers, mixing for 10 minutes at a stirring rate of 50 rpm and a temperature of 180° C., discharging the materials, and preparing a biodegradable plastic;

[0046] An application for biodegradable plastics, comprising the following steps: feeding the biodegradable plastics into a film-making machine, preheating the plastics at a preheating temperature of 190° C. for 5 minutes, hot pressing for 1 minute at a pressure of 10 MPa, and then annealing for 30 minutes at a temperature of 110° C. and a pressure of 10 MPa to obtain a biodegradable film;

[0047] The flame retardant microspheres are prepared by the following steps:

[0048] Step A1: 4-bromo-1-butene, sodium sulfate and deionized water are mixed, and the mixture is reacted for 10 hours at a stirring rate of 150 rpm and a temperature of 80° C., cooled, and filtered to obtain a filter cake. The filter cake is mixed with phosphorus oxychloride, and the mixture is reacted for 1.5 hours at a stirring rate of 120 rpm and a temperature of 120° C. under nitrogen protection to obtain an intermediate a. 3-butene-1-ol, 4-dimethylaminopyridine, triethylamine and dichloromethane are mixed, and the mixture is stirred at a stirring rate of 150 rpm and a temperature of 5° C., and the intermediate a is added thereto, and the mixture is reacted for 1.5 hours to obtain an intermediate b.

[0049] The amount ratio of 4-bromo-1-butene, sodium sulfate, deionized water and phosphorus oxychloride is 0.035 mol: 5-7 g: 35 mL: 30 mL, and the amount ratio of 3-butene-1-ol, 4-dimethylaminopyridine, triethylamine and intermediate a is 0.035 mol: 0.4 g: 6 mL: 0.03 mol;

[0050] Step A2: Mix the intermediate b, styrene, maleic anhydride and isoamyl acetate, stir and add azobisisobutyronitrile under nitrogen protection, at a stirring rate of 120 rpm and a temperature of 70°C, and react for 6 hours to obtain copolymer microspheres; mix the copolymer microspheres with an ethanol solution, stir and add ethylenediamine at a stirring rate of 120 rpm and room temperature, and react for 8 hours to obtain amino copolymer microspheres;

[0051] The amount ratio of intermediate b, styrene, maleic anhydride, isoamyl acetate and azobisisobutyronitrile is 0.035 mol: 0.048 mol: 0.052 mol: 160 mL: 0.1 g, the volume fraction of the ethanol solution is 50%, and the amount ratio of the copolymer microspheres, the ethanol solution and ethylenediamine is 2.4 g: 50 mL: 0.05 mol;

[0052] Step A3: The amino copolymer microspheres and the ethanol solution were mixed, stirred at a stirring rate of 120 rpm and a temperature of 70° C., and the phytic acid aqueous solution was added, and the reaction was carried out for 12 hours. Then, nickel chloride hexahydrate was added and the temperature was raised to 100° C., and the reaction was continued for 3 hours to obtain flame retardant microspheres;

[0053] The volume concentration of the ethanol solution is 80%, the mass concentration of the phytic acid aqueous solution is 70%, and the dosage ratio of the amino copolymer microspheres, the ethanol solution, the phytic acid aqueous solution and the nickel chloride hexahydrate is 2.5g:180mL:10mL:3g;

[0054] The modified filler is prepared by the following steps:

[0055] Step B1: D-gluconic acid solution, methanol and concentrated hydrochloric acid were mixed, and the mixture was reacted for 6 hours at a stirring rate of 180 rpm and a temperature of 60°C. 2-methoxy-4-nitrobenzaldehyde was then added, and the reaction was continued for 24 hours to obtain intermediate 1. Intermediate 1, palladium-carbon catalyst and ethanol were mixed, and the mixture was stirred at a stirring rate of 200 rpm and a temperature of 90°C, and hydrazine hydrate was added, and the reaction was continued for 12 hours to obtain intermediate 2;

[0056] The mass fraction of D-gluconic acid solution is 50%, the mass fraction of concentrated hydrochloric acid is 37%, the amount ratio of D-gluconic acid solution, methanol, concentrated hydrochloric acid and 2-methoxy-4-nitrobenzaldehyde is 115g:100mL:120mL:0.35mol, and the amount ratio of intermediate 1, palladium carbon catalyst and hydrazine hydrate is 0.32mol:4g:30mL;

[0057] Step B2: Mix the intermediate 2, 1,4-dioxane and triethylamine, stir at a stirring rate of 240 rpm and a temperature of 15°C, add cyanuric chloride, react for 2 hours, then heat to 60°C and add γ-aminopropyltriethoxysilane, react for 6 hours to obtain the intermediate 3;

[0058] The amount ratio of intermediate 2, triethylamine, cyanuric chloride and γ-aminopropyltriethoxysilane is 0.05 mol: 2.5 mL: 0.04 mol: 10 g;

[0059] Step B3: Mix commercially available Mayue building materials 1000 mesh calcium carbonate whiskers, deionized water and ethanol and disperse them by ultrasonication for 20 minutes, stir at a stirring rate of 600 rpm and a temperature of 60°C, add intermediate 3, react for 5 hours, filter, and obtain a modified filler;

[0060] The volume ratio of deionized water to ethanol is 1:9, and the amount ratio of calcium carbonate whisker to intermediate 3 is 2g:0.6g.

[0061] Example 3 A production process for biodegradable plastics, comprising the following steps: weighing the following raw materials by weight: 70 parts of commercially available L130 polylactic acid, 4 parts of flame retardant microspheres and 6 parts of modified fillers, mixing the polylactic acid, the flame retardant microspheres and the modified fillers, mixing for 10 minutes at a stirring rate of 50 rpm and a temperature of 180° C., discharging the materials, and preparing a biodegradable plastic;

[0062] An application for biodegradable plastics, comprising the following steps: feeding the biodegradable plastics into a film-making machine, preheating the plastics at a preheating temperature of 190° C. for 5 minutes, hot pressing for 1 minute at a pressure of 10 MPa, and then annealing for 30 minutes at a temperature of 110° C. and a pressure of 10 MPa to obtain a biodegradable film;

[0063] The flame retardant microspheres are prepared by the following steps:

[0064] Step A1: 4-bromo-1-butene, sodium sulfate and deionized water are mixed, and the mixture is reacted for 12 hours at a stirring rate of 150 rpm and a temperature of 80°C, cooled, and filtered to obtain a filter cake. The filter cake is mixed with phosphorus oxychloride, and the mixture is reacted for 1.5 hours at a stirring rate of 150 rpm and a temperature of 120°C under nitrogen protection to obtain an intermediate a. 3-butene-1-ol, 4-dimethylaminopyridine, triethylamine and dichloromethane are mixed, and the mixture is stirred at a stirring rate of 150 rpm and a temperature of 5°C, and the intermediate a is added thereto for a reaction of 1.5 hours to obtain an intermediate b.

[0065] The ratio of 4-bromo-1-butene, sodium sulfate, deionized water and phosphorus oxychloride is 0.035 mol: 7 g: 35 mL: 35 mL, and the ratio of 3-butene-1-ol, 4-dimethylaminopyridine, triethylamine and intermediate a is 0.035 mol: 0.5 g: 6 mL: 0.035 mol;

[0066] Step A2: Mix the intermediate b, styrene, maleic anhydride and isoamyl acetate, stir and add azobisisobutyronitrile under nitrogen protection, at a stirring rate of 120 rpm and a temperature of 70°C, and react for 8 hours to obtain copolymer microspheres; mix the copolymer microspheres with an ethanol solution, stir and add ethylenediamine at a stirring rate of 120 rpm and room temperature, and react for 8 hours to obtain amino copolymer microspheres;

[0067] The amount ratio of intermediate b, styrene, maleic anhydride, isoamyl acetate and azobisisobutyronitrile is 0.035 mol: 0.05 mol: 0.052 mol: 160 mL: 0.15 g, the volume fraction of the ethanol solution is 50%, and the amount ratio of the copolymer microspheres, the ethanol solution and ethylenediamine is 2.4 g: 60 mL: 0.06 mol;

[0068] Step A3: The amino copolymer microspheres and the ethanol solution were mixed, stirred at a stirring rate of 120 rpm and a temperature of 70° C., and the phytic acid aqueous solution was added, and the reaction was carried out for 12 hours. Then, nickel chloride hexahydrate was added and the temperature was raised to 100° C., and the reaction was continued for 4 hours to obtain flame retardant microspheres;

[0069] The volume concentration of the ethanol solution is 80%, the mass concentration of the phytic acid aqueous solution is 70%, and the dosage ratio of the amino copolymer microspheres, the ethanol solution, the phytic acid aqueous solution and the nickel chloride hexahydrate is 2.5g:180mL:10mL:4g;

[0070] The modified filler is prepared by the following steps:

[0071] Step B1: D-gluconic acid solution, methanol and concentrated hydrochloric acid were mixed, and the mixture was reacted for 6 hours at a stirring rate of 200 rpm and a temperature of 60°C, and 2-methoxy-4-nitrobenzaldehyde was added, and the reaction was continued for 24 hours to obtain intermediate 1. Intermediate 1, palladium carbon catalyst and ethanol were mixed, and the mixture was stirred at a stirring rate of 200 rpm and a temperature of 90°C, and hydrazine hydrate was added, and the reaction was continued for 12 hours to obtain intermediate 2;

[0072] The mass fraction of D-gluconic acid solution is 50%, the mass fraction of concentrated hydrochloric acid is 37%, the amount ratio of D-gluconic acid solution, methanol, concentrated hydrochloric acid and 2-methoxy-4-nitrobenzaldehyde is 120g:100mL:150mL:0.35mol, and the amount ratio of intermediate 1, palladium carbon catalyst and hydrazine hydrate is 0.32mol:5g:35mL;

[0073] Step B2: Mix the intermediate 2, 1,4-dioxane and triethylamine, stir at a stirring rate of 240 rpm and a temperature of 15°C, add cyanuric chloride, react for 3 hours, then heat to 60°C and add γ-aminopropyltriethoxysilane, react for 6 hours to obtain the intermediate 3;

[0074] The amount ratio of intermediate 2, triethylamine, cyanuric chloride and γ-aminopropyltriethoxysilane is 0.05 mol: 2.5 mL: 0.05 mol: 10 g;

[0075] Step B3: Mix commercially available Mayue building materials 1000 mesh calcium carbonate whiskers, deionized water and ethanol and disperse them by ultrasonication for 20 minutes, stir at a stirring rate of 800 rpm and a temperature of 60°C, add intermediate 3, react for 4 hours, filter, and obtain a modified filler;

[0076] The volume ratio of deionized water to ethanol is 1:9, and the amount ratio of calcium carbonate whisker to intermediate 3 is 3g:0.6g.

[0077] Comparative Example 1 Compared with Example 3, this comparative example is characterized in that the intermediate b in the preparation process of the flame retardant microspheres in Example 3 is replaced by 1,8-nonadiene, and the other steps are the same.

[0078] Comparative Example 2 Compared with Example 3, this comparative example removes nickel chloride hexahydrate in the preparation process of flame retardant microspheres in Example 3, and the other steps are the same.

[0079] Comparative Example 3 Compared with Example 3, this comparative example is characterized in that the intermediate 2 in the preparation process of the modified filler in Example 3 is replaced by aniline, and the other steps are the same.

[0080] Comparative Example 4 Compared with Example 3, this comparative example is characterized in that the intermediate 3 in the preparation process of the modified filler in Example 3 is replaced by γ-aminopropyltriethoxysilane, and the other steps are the same.

[0081] Take the biodegradable plastics prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, refer to CB / T 1040.1-2006, make them into 20mm×4mm×1mm dumbbell-shaped specimens, the tensile rate is 2mm / min, and test their mechanical properties. Refer to ASTM D256-2010, make them into 65mm×12mm×4mm specimens, V-notch, and test their cantilever beam notch impact strength. Make the biodegradable plastic into a 10mm×10mm×0.1mm sample, put it into a protease buffer solution with a concentration of 0.2mg / mL, the pH value of the buffer solution is 8, shake it on a shaker at a temperature of 45°C and a speed of 130rpm for 5d, weigh it, and calculate its mass loss rate to evaluate its biodegradability. Refer to GB / T 2406-2009, make the biodegradable plastic into a 130mm×6.5mm×3.2mm sample, and test its limiting oxygen index. Refer to GB / T 2408-2008, biodegradable plastics were made into 130mm×13mm×3.2mm samples and subjected to vertical burning grade test. The test results are as follows:

[0082]

[0083] It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, Comparative Example 1 replaces the intermediate b in the preparation process of the flame-retardant microspheres of Example 3 with 1,8-nonadiene. Due to the lack of sulfonate groups, its biodegradability and mechanical properties decrease to a certain extent. Comparative Example 2 removes nickel chloride hexahydrate in the preparation process of the flame-retardant microspheres of Example 3. Due to the lack of nickel ions, its flame retardant properties decrease significantly. Comparative Example 3 replaces intermediate 2 in the preparation process of the modified filler of Example 3 with aniline. Due to the lack of glucose structure, its mechanical properties decrease significantly. Comparative Example 4 replaces intermediate 3 in the preparation process of the modified filler of Example 3 with γ-aminopropyltriethoxysilane. Due to the lack of triazine groups and glucose structures, its flame retardant and mechanical properties decrease significantly.

[0084] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0085] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A production process for biodegradable plastics, characterized in that: The method comprises the following steps: weighing the following raw materials in parts by weight: 60-70 parts of polylactic acid, 3-4 parts of flame retardant microspheres and 5-6 parts of modified fillers, mixing the polylactic acid, the flame retardant microspheres and the modified fillers, mixing for 10 minutes at a stirring rate of 50 rpm and a temperature of 180°C, discharging the materials, and preparing a biodegradable plastic.

2. A process for producing biodegradable plastics according to claim 1, characterized in that: The flame retardant microspheres are prepared by the following steps: Step A1: 4-bromo-1-butene, sodium sulfate and deionized water are mixed, and the mixture is reacted for 10-12 hours at a stirring rate of 120-150 rpm and a temperature of 80° C., cooled, filtered, and a filter cake is obtained. The filter cake is mixed with phosphorus oxychloride, and the mixture is reacted for 1-1.5 hours at a stirring rate of 120-150 rpm and a temperature of 120° C. under nitrogen protection to obtain an intermediate a. 3-butene-1-ol, 4-dimethylaminopyridine, triethylamine and dichloromethane are mixed, and the mixture is stirred at a stirring rate of 120-150 rpm and a temperature of 5° C., and the intermediate a is added thereto for a reaction of 1-1.5 hours to obtain an intermediate b. Step A2: Mix the intermediate b, styrene, maleic anhydride and isoamyl acetate, stir and add azobisisobutyronitrile under nitrogen protection, at a stirring rate of 100-120 rpm and a temperature of 70°C, and react for 6-8 hours to obtain copolymer microspheres, mix the copolymer microspheres with an ethanol solution, stir and add ethylenediamine at a stirring rate of 100-120 rpm and room temperature, and react for 6-8 hours to obtain amino copolymer microspheres; Step A3: The amino copolymer microspheres and the ethanol solution are mixed, stirred at a stirring rate of 100-120 rpm and a temperature of 70°C, and the phytic acid aqueous solution is added, and the reaction is carried out for 12 hours. Then, nickel chloride hexahydrate is added and the temperature is raised to 100°C, and the reaction is continued for 3-4 hours to obtain flame retardant microspheres.

3. A process for producing biodegradable plastics according to claim 2, characterized in that: In step A1, the usage ratio of 4-bromo-1-butene, sodium sulfate, deionized water and phosphorus oxychloride is 0.03-0.035 mol: 5-7 g: 30-35 mL: 30-35 mL, and the usage ratio of 3-butene-1-ol, 4-dimethylaminopyridine, triethylamine and intermediate a is 0.03-0.035 mol: 0.4-0.5 g: 5-6 mL: 0.03-0.035 mol.

4. A process for producing biodegradable plastics according to claim 2, characterized in that: In step A2: the amount ratio of intermediate b, styrene, maleic anhydride, isoamyl acetate and azobisisobutyronitrile is 0.03-0.035 mol: 0.048-0.05 mol: 0.05-0.052 mol: 150-160 mL: 0.1-0.15 g, the volume fraction of the ethanol solution is 50%, and the amount ratio of the copolymer microspheres, the ethanol solution and ethylenediamine is 2-2.4 g: 50-60 mL: 0.05-0.06 mol.

5. A process for producing biodegradable plastics according to claim 2, characterized in that: In step A3: the volume concentration of the ethanol solution is 80%, the mass concentration of the phytic acid aqueous solution is 70%, and the amount ratio of the amino copolymer microspheres, the ethanol solution, the phytic acid aqueous solution and the nickel chloride hexahydrate is 2.2-2.5g:150-180mL:8-10mL:3-4g.

6. A process for producing biodegradable plastics according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step B1: D-gluconic acid solution, methanol and concentrated hydrochloric acid are mixed, and the mixture is reacted for 4-6 hours at a stirring rate of 180-200 rpm and a temperature of 60°C, and 2-methoxy-4-nitrobenzaldehyde is added, and the reaction is continued for 24 hours to obtain intermediate 1. Intermediate 1, palladium carbon catalyst and ethanol are mixed, and the mixture is stirred at a stirring rate of 180-200 rpm and a temperature of 90°C, and hydrazine hydrate is added, and the reaction is carried out for 12 hours to obtain intermediate 2; Step B2: Mix the intermediate 2, 1,4-dioxane and triethylamine, stir at a stirring rate of 200-240 rpm and a temperature of 15° C., add cyanuric chloride, react for 2-3 hours, then heat to 60° C. and add γ-aminopropyltriethoxysilane, react for 4-6 hours to obtain the intermediate 3; Step B3: Calcium carbonate whiskers, deionized water and ethanol are mixed and ultrasonically dispersed for 20 minutes. Under stirring conditions of 600-800 rpm and 60° C., intermediate 3 is added and reacted for 4-5 hours. The mixture is filtered to obtain a modified filler.

7. A process for producing biodegradable plastics according to claim 6, characterized in that: In step B1, the mass fraction of D-gluconic acid solution is 50%, the mass fraction of concentrated hydrochloric acid is 37%, the amount ratio of D-gluconic acid solution, methanol, concentrated hydrochloric acid and 2-methoxy-4-nitrobenzaldehyde is 115-120g:80-100mL:120-150mL:0.3-0.35mol, and the amount ratio of intermediate 1, palladium carbon catalyst and hydrazine hydrate is 0.3-0.32mol:4-5g:30-35mL.

8. A process for producing biodegradable plastics according to claim 6, characterized in that: In step B2: the usage ratio of intermediate 2, triethylamine, cyanuric chloride and γ-aminopropyltriethoxysilane is 0.04-0.05 mol: 2.5 mL: 0.04-0.05 mol: 8-10 g.

9. The process for producing biodegradable plastics according to claim 6 is characterized by: In step B3: the volume ratio of deionized water to ethanol is 1:9, and the amount ratio of calcium carbonate whiskers to intermediate 3 is 2-3g:0.5-0.6g.

10. An application for biodegradable plastics, characterized in that: The method comprises the following steps: feeding the biodegradable plastic into a film-making machine, preheating the film for 5 minutes at a preheating temperature of 190° C., hot pressing the film for 1 minute at a pressure of 10 MPa, and annealing the film for 30 minutes at a temperature of 110° C. and a pressure of 10 MPa to obtain a biodegradable film.